On Optimization Strategies for Inverse Problems in Metalforming - Söhngen, Benjamin; Caspari, Michael; Willner, Kai; Steinmann, Paul (Sheet Bulk Metal Forming - Research Results of the TCRC73, 2020)
In this contribution we consider inverse mechanical problems in terms of parameter identification and shape optimization. The fundamental material behavior is thereby modelled with an elasto-plastic constitutive law based on the logarithmic strain space, considering anisotropic yield and kinematic hardening. The identification of the constitutive material parameters is based on the virtual fields method (VFM) minimizing the gap between external and internal virtual work. By using a strategy with relation to a stress sensitivity analysis, the virtual fields can be obtained automatically. A specifically designed cruciform specimen, which produces heterogeneous deformation states, is used with a biaxial testing machine. For the shape optimization, a Newton iteration step is deduced to iteratively minimize the differences between desired and deformed shape of a forming simulation. The presented inverse, node-based algorithm covers a wide range of applications, since all requirements of a forming process are fulfilled. The method is demonstrated by means of a backward extrusion process.<br